Stability of the Resistance to the Thiosemicarbazone Derived from 5,6-Dimethoxy-1-Indanone, a Non-Nucleoside Polymerase Inhibitor of Bovine Viral Diarrhea Virus - Castro, Eliana F. (Public Library of Science, 2014)
Bovine viral diarrhea virus (BVDV) is the prototype Pestivirus. BVDV infection is distributed worldwide and causes serious problems for the livestock industry. The thiosemicarbazone of 5,6-dimethoxy-1-indanone (TSC) is a non-nucleoside polymerase inhibitor (NNI) of BVDV. All TSC-resistant BVDV variants (BVDV-TSC(r) T(1–5)) present an N264D mutation in the NS5B gene (RdRp) whereas the variant BVDV-TSC(r) T(1) also presents an NS5B A392E mutation. In the present study, we carried out twenty passages of BVDV-TSC(r) T(1–5) in MDBK cells in the absence of TSC to evaluate the stability of the resistance. The viral populations obtained (BVDV R(1–5)) remained resistant to the antiviral compound and conserved the mutations in NS5B associated with this phenotype. Along the passages, BVDV R(2), R(3) and R(5) presented a delay in the production of cytopathic effect that correlated with a decrease in cell apoptosis and intracellular accumulation of viral RNA. The complete genome sequences that encode for NS2 to NS5B, Npro and Erns were analyzed. Additional mutations were detected in the NS5B of BVDV R(1), R(3) and R(4). In both BVDV R(2) and R(3,) most of the mutations found were localized in NS5A, whereas in BVDV R(5), the only mutation fixed was NS5A V177A. These results suggest that mutations in NS5A could alter BVDV cytopathogenicity. In conclusion, the stability of the resistance to TSC may be due to the fixation of different compensatory mutations in each BVDV-TSC(r). During their replication in a TSC-free medium, some virus populations presented a kind of interaction with the host cell that resembled a persistent infection: decreased cytopathogenicity and viral genome synthesis. This is the first report on the stability of antiviral resistance and on the evolution of NNI-resistant BVDV variants. The results obtained for BVDV-TSC(r) could also be applied for other NNIs.